(6x-3)+2=5x

Simple and best practice solution for (6x-3)+2=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-3)+2=5x equation:


Simplifying
(6x + -3) + 2 = 5x

Reorder the terms:
(-3 + 6x) + 2 = 5x

Remove parenthesis around (-3 + 6x)
-3 + 6x + 2 = 5x

Reorder the terms:
-3 + 2 + 6x = 5x

Combine like terms: -3 + 2 = -1
-1 + 6x = 5x

Solving
-1 + 6x = 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-1 + 6x + -5x = 5x + -5x

Combine like terms: 6x + -5x = 1x
-1 + 1x = 5x + -5x

Combine like terms: 5x + -5x = 0
-1 + 1x = 0

Add '1' to each side of the equation.
-1 + 1 + 1x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 1x = 0 + 1
1x = 0 + 1

Combine like terms: 0 + 1 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| 4k-4k-1=48 | | (3z-8)(z+5)=0 | | -2t+11t+(5+-9)t= | | -1/4+-3/4= | | -72=6w | | kx=-2 | | 4-3(5*0)+2= | | 10x-7+3x=5x+7-8x | | 4x-4=6x+7 | | 5/2x-7=3/4x+14 | | 2+2f=4 | | 5/4x-2=3/2x-4 | | x^2-64=60 | | 5/4x-9=3/2x-12 | | 32y-44= | | (-b-5x-3)+(2b-4x+7)= | | 5/2x+7/2=3/4x+14 | | 7.5c-2.5c+8=-7 | | m=6x | | 4.6y-y+4=y-1.2 | | 5m+3=4m+5 | | PFcmN44a2qyyu®a-//A©aecu6 | | 3.2b-4.7=3b-3.3 | | 1/4x+5/3x-4=2-1/12x | | 8x+-4=12 | | 4(x+10)=19 | | i^3= | | y-1(3+66)+12=1203 | | x-2*x*sqrt(z)+5*z=1 | | 3(x-5)-3x^2=-30 | | y-1(3-66)+12=1203 | | 8(2x+3)=48 |

Equations solver categories